2011
DOI: 10.1089/glre.2011.151006
|View full text |Cite
|
Sign up to set email alerts
|

Problem Gambling in the Correctional System: A Brief Summary Report

Abstract: A mong the most troublesome and least understood consequence of problem gambling is gambling-related crime. According to Abbott, McKenna, and Giles, 1 between one-third and twothirds of problem gamblers engaged in treatment or mutual help groups report having committed gambling-related offenses. Studies of the general population in Canada and in the United States have found that approximately 1% of the population may be pathological gamblers, and that between 2% and 3% of the population suffer from subclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Therefore, driving under the influence after leaving a casino is less often the reason for an arrest. In Canada, people with gambling problems often enter the criminal justice system because they are charged with theft (79.2%), possession of property obtained by crime (79.2%), break and entry (58.3%), robbery (50%.0), fraud (33.3%), or other financial crimes (Turner & McAvoy, 2011).…”
Section: Diversion To Problem-solving Courtsmentioning
confidence: 99%
“…Therefore, driving under the influence after leaving a casino is less often the reason for an arrest. In Canada, people with gambling problems often enter the criminal justice system because they are charged with theft (79.2%), possession of property obtained by crime (79.2%), break and entry (58.3%), robbery (50%.0), fraud (33.3%), or other financial crimes (Turner & McAvoy, 2011).…”
Section: Diversion To Problem-solving Courtsmentioning
confidence: 99%
“…Both the connection between gambling and crime and that between gambling and social disadvantage are well established. Numerous studies have found higher rates of problem gambling among criminal offenders than in the general population (Turner and McAvoy 2011;May-Chahal et al 2017;Turner et al 2017;Moore 2018;Riley et al 2018;Lind et al 2019;Widinghoff et al 2019;Banks et al 2020). Although only a relatively small proportion of all crime is gambling-related (Arthur et al 2014), a study on British prisoners estimated that problem gambling is linked with up to 13% of all offending (May-Chahal et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Given these limitations in our current knowledge the objective of the current research was to explore expert opinions on barriers to treatment, sex or gender differences for disordered gambling in a correctional setting, and the best approach to dealing with gambling problems in a correctional setting (e.g., a specific gambling treatment program or have problem gambling integrated into more general programs). This study was also part of a larger project that has used mixed methods including questionnaires and interviews with P-CJI, official records, and interviews with professionals who work with P-CJI, to study the prevalence of problem gambling among P-CJI (Turner et al, 2009; Turner et al, 2013b), crimes committed (Turner et al, 2009; Turner & McAvoy, 2011), their mental health problems (Preston et al, 2012), and examine programs that have been offered to P-CJI with gambling problems (Turner et al, 2017). Because of the dearth of research on this topic, we conducted semi-structured interviews with key experts in the field to explore the state of programming for people in the correctional system with a gambling disorder.…”
Section: Introductionmentioning
confidence: 99%